Pelatihan UMKM Produk Desa Ponggang - wahju, Marsellinus Bachtiar; Lukas, Lukas; Widawati, Enny (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2022)
Pong's Snack is an MSMEs originating from Ponggang Village that produces various types of snacks such as opak, rengginang, cassava chips, wajid, potato chips, taro chips, banana chips, Seroja, kicimpring, and cistik. MSMEs in Ponggang Village still use conventional methods, such as marketing products by entrusting them to stalls, can order in advance via telephone number and the product is delivered directly to the customer. Therefore, the author helps MSMEs to be better known to the wider community by entering the products produced by MSMEs into the Pareang Sate Restaurant and selling their products online through the Tokopedia application. To be able to market products online, it is necessary to take steps that can be used as guidelines in digital marketing activities aimed at the target market and known as AIDA (Awareness, Interest, Desire, and Action). The first step taken by the author so that Pong's Snack MSMEs products can be known to consumers is to build awareness of consumers by using the 7P product, price, place, promotion, people, process, and physical evidence approach. To increase interest in buying a product, a standing pouch is used an attractive label and packaging design.